Case Report: Successful Repair of Primary Aortoesophageal Fistula With an Endovascular Stent Graft and an Esophageal Stent - Wu, Zhi-Wei; Yao, Yong-Dong; Li, Yi-Ming (Frontiers in Surgery, 2022)
Aortoesophageal fistula (AEF), secondary to thoracic pseudoaneurysm as a result of upper gastrointestinal bleeding, is a rare condition and will be undoubtedly lethal without prompt surgical intervention. The estimated annual incidence of primary AEFs and secondary AEFs is about 0.0015% and 0.6%–2%, respectively. The challenges of the therapy posed by AEF are control of the hemorrhage, arterial reconstruction in an infection field, control of sepsis, and re-establishment of the alimentary tract. We present a case of a 58-year-old man who suffered from chest pain and hematemesis and was finally diagnosed with pAEF caused by descending thoracic pseudoaneurysm. Our team successfully deployed an endovascular stent graft and esophageal stent to seal ruptured thoracic aorta and esophageal defects, which provided a new surgical strategy for aortoesophageal fistula in the endovascular era.